The importance of continuing surveillance of risk factors for prevention of cardiovascular diseases (Italian Journal of Public Health, 2007)
After peaking in the 1960s’, cardiovascular diseases (CVDs) have shown a consistent decline in western countries in recent decades [1].Despite this,CVDs remain the major cause of mortality and morbidity in industrialized populations, with relevant associated socio-economical issues, while their incidence is increasing in developing countries. Several factors have likely contributed to the reduced incidence of CVDs in industrialized societies, including an increase in education and attention to health issues, lifestyle changes and improvement in diagnostic facilities and therapeutic tools. Epidemiologic studies have played an outstanding role in the decline of CVDs. Indeed, they have allowed for the identification of habits and conditions which expose healthy subjects to an increased risk of development of atherosclerosis and its complications They have also led to the implementation of appropriate programs and campaigns aimed at fighting the identified risk factors by means of changes in diet and lifestyle and the use of specific drug treatments. In particular, tight control and prevention of hypertension, smoking and hypercholesterolemia has largely contributed to the reduction of CVDs, accounting for more than 50% of the reduction of mortality from the 1960s’ to the 1990s’ [2].This approach was also crucial in improving the clinical outcomes of secondary prevention for CVDs.